Gene expression profiles and protein-protein interaction networks in THP-1 cells exposed to metal-based nanomaterials - Šíma, Michal; Líbalová, Helena; Závodná, Táňa; Vrbová, Kristýna; Kléma, Jiří; Rössner, Pavel (Environmental toxicology and pharmacology, 2024)
We analyzed gene expression in THP-1 cells exposed to metal-based nanomaterials (NMs) [TiO2 (NM-100), ZnO (NM-110), SiO2 (NM-200), Ag (NM-300 K)]. A functional enrichment analysis of the significant differentially expressed genes (DEGs) identified the key modulated biological processes and pathways. DEGs were used to construct protein-protein interaction networks. NM-110 and NM-300 K induced changes in the expression of genes involved in oxidative and genotoxic stress, immune response, alterations of cell cycle, detoxification of metal ions and regulation of redox-sensitive pathways. Both NMs shared a number of highly connected protein nodes (hubs) including CXCL8, ATF3, HMOX1, and IL1B. NM-200 induced limited transcriptional changes, mostly related to the immune response; however, several hubs (CXCL8, ATF3) were identical with NM-110 and NM-300 K. No effects of NM-100 were observed. Overall, soluble nanomaterials NM-110 and NM-300 K exerted a wide variety of toxic effects, while insoluble NM-200 induced immunotoxicity; NM-100 caused no detectable changes on the gene expression level.
Keywords: mapy interakcí proteinů; Transcriptome; oxid křemičitý; hemoxygenasa-1; Titanium; Heme Oxygenase-1; Protein Interaction Maps; transkriptom; Silver; transkripční faktor ATF3; Nanostructures; Silicon Dioxide; oxid zinečnatý; nanostruktury; THP-1 Cells; Metal Nanoparticles; THP-1 buňky; Interleukin-8; interleukin-8; titan; kovové nanočástice; Activating Transcription Factor 3; Zinc Oxide; lidé; Humans; stříbro